Reporting of Mammary Tumours in Sprague Dawley/NIN Mutant (Hairless) Rat Strain. (Journal of Laboratory Animal Science, 2024)
A spontaneous genetic mutation in Sprague Dawley rats was detected at the ICMR-NIN animal facility.  The spontaneously mutated rat was examined for body composition, serum biochemistry, peripheral  blood CD4 and CD8 cell population, and spontaneous tumour growth. We observed the spontaneous  development of tumours in 24 animals on crossbreeding. The animals showed no significant  differences in vital organ structure as compared to the heterozygous animals. Interestingly, both  homozygous (hairless) and heterozygous rats developed spontaneous fibroadenomas in their  mammary glands during adulthood, which was distinct from the parent NIN/SD rat colony. Importantly,  there was no connection between the biochemical and T cell population and the presence of these  tumours. The histological characteristics of the tumours closely resembled mammary tumours in  humans. In conclusion, the hairless SD rat model with thymus will serve as a valuable tool in cancer  research, particularly in mammary tumour studies.
Keywords: Hairless rat; Sprague Dawley; mammary tumour